T‐SNAREs bind the Rhg1 α‐SNAP and mediate soybean cyst nematode resistance. (6th August 2020) - Dong, Jia; Zielinski, Raymond E.; Hudson, Matthew E.
Summary: Soybean cyst nematode (SCN; Heterodera glycines ) is the largest pathogenic cause of soybean yield loss. The Rhg1 locus is the most used and best characterized SCN resistance locus, and contains three genes including one encoding an α‐SNAP protein. Although the Rhg1 α‐SNAP is known to play an important role in vesicle trafficking and SCN resistance, the protein's binding partners and the molecular mechanisms underpinning SCN resistance remain unclear. In this report, we show that the Rhg1 α‐SNAP strongly interacts with two syntaxins of the t‐SNARE family (Glyma.12G194800 and Glyma.16G154200) in yeast and plants; importantly, the genes encoding these syntaxins co‐localize with SCN resistance quantitative trait loci. Fluorescent visualization revealed that the α‐SNAP and the two interacting syntaxins localize to the plasma membrane and perinuclear space in both tobacco epidermal and soybean root cells. The two syntaxins and their two homeologs were mutated, individually and in combination, using the CRISPR‐Cas9 system in the SCN‐resistant Peking and SCN‐susceptible Essex soybean lines. Peking roots with deletions introduced into syntaxin genes exhibited significantly reduced resistance to SCN, confirming that t‐SNAREs are critical to resisting SCN infection. The results presented here uncover a key step in the molecular mechanism of SCN resistance, and will be invaluable to soybean breeders aiming to develop highly SCN‐resistant soybean varieties. Significance Statement: Although the soybean cyst nematode (SCN) is the most damaging pathogen of soybeans in the USA, resistance mechanisms are still only partially understood. In this study, we identify two genes encoding syntaxin proteins that interact with a key player in SCN resistance, the Rhg1 α‐SNAP protein. Using the CRISPR/Cas9 system, we knockout these syntaxins in soybean roots and demonstrate they are essential to maintain SCN resistance. These findings will aid in the development of yield‐protecting SCN resistance traits.